2011
DOI: 10.1186/1472-6963-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 50. challenges at work for older nurses and allied health workers in rural Australia: a thematic analysis of focus group discussions

Abstract: BackgroundThe health workforce in Australia is ageing, particularly in rural areas, where this change will have the most immediate implications for health care delivery and workforce needs. In rural areas, the sustainability of health services will be dependent upon nurses and allied health workers being willing to work beyond middle age, yet the particular challenges for older health workers in rural Australia are not well known. The purpose of this research was to identify aspects of work that have become mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 28 publications
3
61
1
Order By: Relevance
“…Similar to a previous study (Fragar & Depczynski ), older nurses in Singapore reported that working with computers was a challenge. This relates to both little prior exposure and the need to adapt to new ways of working brought about by automation of work processes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar to a previous study (Fragar & Depczynski ), older nurses in Singapore reported that working with computers was a challenge. This relates to both little prior exposure and the need to adapt to new ways of working brought about by automation of work processes.…”
Section: Discussionsupporting
confidence: 79%
“…). The definition of ‘older nurse’ varies, some defining it as 46 years and older (Stichler ), others as above the age of 50 (Fragar & Depczynski ; Letvak et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the recognized challenges faced by older nurses in the workplace relate to the physical strain of providing direct patient care in a fast paced environment, which tends to be exacerbated by a high prevalence of musculoskeletal injury, natural physical decline and the requirement to do shift work (Gabrielle et al. ; Phillips & Miltner ; Fragar & Depczynski ). Further reported challenges include a lack of recognition of the skills and experience of the older nurse, inadequate support from colleagues and managers, inter‐generational conflict and mid‐life demands such as home‐life responsibilities, caring for elderly relatives and maintaining personal health and well‐being (Clendon & Walker ; Fitzgerald ; Letvak ; Mion et al.…”
Section: The Ageing Nursing Workforcementioning
confidence: 99%
“…One explanation for the lower proportion of older workers here could be that most of the ACFs in this study employed a large number of international students on 20-hour a week work visas (aged about 20 to 30 years). International student labour (and migrant labour generally) is unlikely to be widely available outside major metropolitan areas, certainly not in the country where staff are older and more Anglo Saxon (Fragar and Depczynski, 2011). Nevertheless, few other industries operate with a significant proportion of their workers aged more than 45 years.…”
Section: Age and Gendermentioning
confidence: 99%